Informação Arquivística: v. 3, n. 2 (2014) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2015)
Link de acesso ao Número:http://www.aaerj.org.br/ojs/index.php/informacaoarquivistica/issue/view/5